2002
DOI: 10.1038/sj.ejcn.1601408
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional association between total level and type of alcohol consumption and glycosylated haemoglobin level: the EPIC-Norfolk Study

Abstract: Objective: To investigate the association between total level and type of alcohol consumed and glycaemia. Design: Cross-sectional study. Setting: The EPIC-Norfolk Study, a population-based cohort study of diet and chronic disease. Subjects and methods: Non-diabetic men (n ¼ 2842) and women (n ¼ 3572), aged 40 -78 y. Alcohol intake was assessed by self-reported questionnaire, and glycaemia measured by glycosylated haemoglobin (HbA 1c ). Results: Ten percent of men and 18% of women reported drinking no alcohol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 49 publications
5
15
0
1
Order By: Relevance
“…This finding agrees with the findings of an inverse relationship between alcohol intake and hemoglobin A1C in previous studies using general populations 30,31) . However, the amount of alcohol intake is recommended to be less than 20-30 g ethanol per day from the viewpoint of prevention of hypertension 21) , and this amount corresponds to the alcohol intake of light drinkers in the present study.…”
Section: A B C D E Fsupporting
confidence: 83%
“…This finding agrees with the findings of an inverse relationship between alcohol intake and hemoglobin A1C in previous studies using general populations 30,31) . However, the amount of alcohol intake is recommended to be less than 20-30 g ethanol per day from the viewpoint of prevention of hypertension 21) , and this amount corresponds to the alcohol intake of light drinkers in the present study.…”
Section: A B C D E Fsupporting
confidence: 83%
“…Among people without diabetes, moderate alcohol consumption may enhance insulin sensitivity [43][44][45][46][47][48][49][50][51] and has been shown to decrease A1C. [52][53][54][55][56] It is plausible that regular, moderate alcohol consumption by people with diabetes similarly enhances insulin sensitivity and improves glycemic control. If this is the case, it might follow that the effect would be greater among type 2 diabetes patients, as they typically have much greater insulin resistance than those with type 1 diabetes; we did not, however, find different patterns of effect by diabetes type in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is still debate, recent systemic reviews of previous prospective studies have shown that moderate alcohol consumption is associated with a decreased incidence of diabetes [10,11]. Coinciding with this, previous cross-sectional studies have shown that glycated hemoglobin, a marker reflecting long-term blood glucose level, was lower in moderate drinkers than in nondrinkers [12,13]. In most of those studies, Western populations were used as subjects.…”
Section: Introductionmentioning
confidence: 99%